Entrepreneurial Ability, Venture Investments, and Risk Sharing - Amit, Raphael; Glosten, Lawrence; Muller, Eitan (Management Science, 1990)
A number of issues that relate to the desirability and implications of new venture financing are examined within a principal-agent framework that captures the essence of the relationship between entrepreneurs and venture capitalists. The model suggests: (1) As long as the skill levels of entrepreneurs are common knowledge, all will choose to involve venture capital investors, since the risk sharing provided by outside participation dominates the agency relationship that is created. (2) The less able entrepreneurs will choose to involve venture capitalists, whereas the more profitable ventures will be developed without external participation because of the adverse selection problem associated with asymmetric information. (3) If a costly signal is available that conveys the entrepreneur's ability, some entrepreneurs will invest in such a signal and then sell to investors; these entrepreneurs, however, need not be the more able ones. The implications for new venture financing of these and other findings are discussed and illustrated by example.